On Time and Planning: Opening Futures by Cultivating a "Sense of Now". (August 2019) - Laurian, Lucie; Inch, Andy
Planning seeks to shape sociospatial outcomes but is also, by nature, future oriented. Yet, planning theory and practice have paid relatively little attention to ongoing debates about changing social relations to time. Building on a wide range of disciplines, we review the multiple temporalities through which lives are lived, the modern imposition of clock time, postmodern acceleration phenomena in the Anthropocene, and their implications for planning's relationship to the past, present, and future and for planning theory. We discuss how thinking more and differently about time might challenge and improve planning by helping theory do better justice to the complexity of practice. We conclude by outlining eight propositions for rethinking planning's relationship to time.